175 INSULIN STIMULATES GENE TRANSCRIPTION BY SEQUENTIAL MODIFICATIONS OF O-GLYCOSYLATION AND PHOSPHORYLATION OF SP1. (1st January 2006) - Hungerford, J.; Majumdar, G.; Raghow, R.; Martinez-Hernandez, A.; Gerling, I.; Solomon, S.
Abstract : Insulin activates calmodulin (CaM) gene transcription, which leads to activation of low Km cAMP phosphodiesterase. This results in reversal of diabetic ketoacidosis. We have previously shown by 32 P labeling experiments and Western blots with antibodies highly specific for Sp1, O-GlcNAc, and phosphoserine that insulin first stimulates synthesis of Sp1 and then O-glycosylates it (early), followed by phosphorylation (later). Transcription of the CaM gene then occurs. H-411E liver cells in tissue culture were incubated with insulin (10, 000 μU/mL) and processed at 0, 30, and 240 min. After incubation, cell extracts were prepared and run on 7.5% SDS polyacrylamide gel. The Sp1 band, localized by SYPRO stain and Western blot using specific anti-Sp1 antibody, was trypsin digested and then analyzed by matrix-assisted laser desorption-ionization time-of-flight mass spectrometry (MALDI TOF MS). The data revealed that at least 3 peptide fragments containing serine/threonine sites are modified either by O-glycosylation or phosphorylation over the period of 4 hr of insulin exposure. The peptides are (1) 612-616; (2) 641-645; and (3) 699-704. The serine sites of these peptides were unmodified at 0 min and O-glycosylated at 30 min and later that same site was converted to a phosphate, eg, one of the three peptide fragments with mass 563.24 kDa (serine 613) is glycosylated at 30 min with a peptide mass of 766.31 kDa (563.24 + 203.19) and then at 240 min deglycosylated and phosphorylated with a peptide of mass of 644.26 (563.24 + 80.9) appearing. Insulin treatment at 0 min shows that the 4 serine sites in these 3 peptides initially are unmodified, but after 30 min all of these serine sites (100%) are O-GlcNAced. Following 4 hr insulin treatment, 3 out of 4 (75%) of the serine sites are phosphorylated. Conclusions: MALDI TOF MS experiments support a yin-yang hypothesis, ie, the existence of a reciprocal relationship between O-glycosylation and phosphorylation of Sp1 and its role in translating insulin's effect on CaM gene transcription.